TANGGUNG JAWAB NEGARA ATAS PEMULIHAN HAK PEREMPUAN DALAM PERIZINAN SAWIT DI INDONESIA: PERSPEKTIF CEDAW - Rastiawaty Rastiawaty; Birkah Latif; Ismail Alrip; Kadarudin (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2026)
Abstract Oil palm licensing in Indonesia is not only related to business legality, but also concerns the protection of women’s human rights, environmental justice, and state responsibility in natural resource governance. Oil palm expansion affects women’s access to land, water, food, health, livelihoods, participation, information, and justice, while the licensing and certification regimes remain largely oriented toward administrative compliance and business sustainability. This article aims to formulate CEDAW-based state responsibility for ensuring women’s right to an effective remedy in response to integrity problems in Indonesia’s oil palm licensing system. This research uses normative legal research with conceptual and comparative approaches. The analysis shows that Indonesian positive law has provided constitutional, human rights, environmental, plantation, business licensing, and sustainable palm oil certification frameworks, but it has not explicitly regulated gender-responsive standards for restoring women’s rights. This weakness is reflected in the absence of gender-responsive human rights due diligence obligations, the lack of integrated indicators for women’s rights restoration in licensing and certification, and fragmented institutional coordination. The novelty of this article lies in the model of state responsibility based on CEDAW due diligence through the concept of gender environmental justice and a limited comparison with Malaysia. The study concludes that the state has an active obligation to prevent, protect, fulfill, and restore women’s rights in oil palm licensing. Oil palm licensing should be directed toward a CEDAW based gender responsive due diligence model so that women’s right to an effective remedy becomes an integral part of oil palm governance in Indonesia.